Sociology in our times - Kendall, Diana (Thomson,Wadsworth, 2007)
Includes bibliographical references (p. 689-719) and indexes.; Contains twenty carefull written, well - organized chapters to introduce students to the best of sociological thinking. This edition buids on the best from previous edition while providing students with new insights and learning tools. New to this edition are Media Framing boxes, which have been added to many of the chapters to demonstrate the process by which information and intertainment are packaged by the mass media (newpapers, magazines, radio, internet...). SociologyNow also provides students with a number of interactive exercises and activities designed to help them review the concepts covered in each chapter.